2020
DOI: 10.1007/s11357-020-00276-z
|View full text |Cite
|
Sign up to set email alerts
|

Association of physical activity and sedentary time with structural brain networks—The Maastricht Study

Abstract: We assessed whether objectively measured low- and high-intensity physical activity (LPA and HPA) and sedentary time (ST) were associated with white matter connectivity, both throughout the whole brain and in brain regions involved in motor function. In the large population-based Maastricht Study (n = 1715, age 59.6 ± 8.1 (mean ± standard deviation) years, and 48% women), the amounts of LPA, HPA, and ST were objectively measured during 7 days by an activPAL accelerometer. In addition, using 3T structural and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 36 publications
0
14
0
1
Order By: Relevance
“…Brain structure. Associations between different intensities of physical activity and brain structure were examined in 3 cross-sectional studies (41,56,67). Overall, average minutes per day of physical activity accumulated at different intensities was not associated with basal ganglia, primary motor cortex, parietal lobe, and occipital lobe volume (56).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Brain structure. Associations between different intensities of physical activity and brain structure were examined in 3 cross-sectional studies (41,56,67). Overall, average minutes per day of physical activity accumulated at different intensities was not associated with basal ganglia, primary motor cortex, parietal lobe, and occipital lobe volume (56).…”
Section: Resultsmentioning
confidence: 99%
“…Associations between different intensities of physical activity and brain structure were examined in 3 cross-sectional studies (41,56,67). Overall, average minutes per day of physical activity accumulated at different intensities was not associated with basal ganglia, primary motor cortex, parietal lobe, and occipital lobe volume (56). Average time in "moderate-to-vigorous" physical activity, but not in "light" intensity, was positively associated with left hippocampal volume (41), and average times in "light" and "moderateto-vigorous" physical activity were associated with higher total cerebral brain volume (67).…”
Section: Resultsmentioning
confidence: 99%
“…13 A recent population-based study observed motor cortex and basal ganglia structural connectivity to be positively associated with physical activity. 45 Thus, the effects of physical activity on white matter microstructure may be largely confined to structural connectivity between regions involved in motor functions.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it is unclear how physical activity and sedentary behavior effect early brain function changes. Physical inactivity and sedentary behavior have been linked to structural brain alterations such as neurodegeneration and cerebral small artery disease, and there is a definite link between the variables [7][8][9] . While atrophy and cerebral microvascular disease are almost certainly irreversible, new indications of early reversible brain changes may be present in individuals as concerns 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Physical inactivity and sedentary behavior have been linked to structural brain alterations such as neurodegeneration and cerebral small artery disease, and there is a definite link between the variables [7][8][9] . While atrophy and cerebral microvascular disease are almost certainly irreversible, new indications of early reversible brain changes may be present in individuals as concerns 8 . Physical inactivity is a known global public health problem that is increasing in prevalence and has a harmful effect on disease patterns everywhere.…”
Section: Introductionmentioning
confidence: 99%